Uncovering Halal Label Food Purchase Intention Behavior in Indonesia: A Twitter Analytics and SEM-Based Investigation - Nadia Nurul Izza; Nashr Akbar (Universitas Airlangga, 2023)
ABSTRACT This study examined the factors that influence the intention to buy food labeled halal among Muslim consumers in Indonesia using mixed methods, this research used qualitative analysis by identifying trending topics related to 2.665 conversations on halal labels on Twitter in Indonesia using Drone Emprit Academic (DEA) and NVivo 12 Plus to uncover the underlying perception. A quantitative hypothesis was then developed based on the qualitative investigation and the adoption literature. Survey data was collected from 407 Muslim consumers in Indonesia using SEM-PLS. The results showed that the variables halal labeled food intention, halal labeled food safety, and halal labeled food knowledge showed a significant and positive influence on the intention to buy halal labeled food and repeat purchases of halal labeled food. This shows increasing consumer awareness about product halalness, health, and perceived value, which in turn encourages consumer interest to buy food products labeled halal. Keywords: purchase intention; halal-labelled food; mixed-methods ABSTRAK Penelitian ini mengkaji faktor-faktor yang memengaruhi minat beli makanan berlabel halal di kalangan konsumen muslim di Indonesia dengan menggunakan metode campuran. analisis kualitatif dengan mengidentifikasi trending topik terkait 2.665 percakapan label halal di Twitter menggunakan Drone Emprit Academic (DEA) dan NVivo 12 Plus untuk mengungkap persepsi yang mendasarinya. Hipotesis kuantitatif kemudian dikembangkan berdasarkan penyelidikan kualitatif dan literatur adopsi. Data survei dikumpulkan dari 407 konsumen muslim dan dianalisis menggunakan pendekatan SEM-PLS. Hasilnya variabel niat makanan berlabel halal, keamanan makanan berlabel halal, dan pengetahuan makanan berlabel halal menunjukkan pengaruh yang signifikan dan positif terhadap niat beli makanan berlabel halal dan pengulangan pembelian makanan berlabel halal. Hal ini menunjukkan meningkatnya kesadaran konsumen tentang kehalalan produk, kesehatan, dan nilai yang dirasakan, yang selanjutnya mendorong minat konsumen untuk membeli produk makanan berlabel halal. Kata Kunci: niat beli; makanan berlabel halal; mixed methods